Pomegranate and Its Components, Punicalagin and Ellagic Acid, Promote Antidepressant, Antioxidant, and Free Radical-Scavenging Activity in Ovariectomized Rats - Cervantes-Anaya, Nancy; Azpilcueta-Morales, Gabriel; Estrada-Camarena, Erika; Ramírez Ortega, Daniela; Pérez de la Cruz, Veronica; González-Trujano, Maria Eva; López-Rubalcava, C. (Frontiers in Behavioral Neuroscience, 2022)
Based on previous reports where the antidepressant-like action of the aqueous extract of pomegranate (Punica granatum: AEPG) was described, we evaluated the effect of AEPG pre-treatment on the redox environment (reactive oxygen species [ROS] production, lipoperoxidation [LPX], and cellular function) in the brain and liver from ovariectomized rats exposed ex vivo to pro-oxidants. Also, as possible active compounds, we selected punicalagin and ellagic acid to study their antidepressant-like effects (0.001, 0.01, 0.1, 1.0, and 10 mg/kg) in the forced swimming test, and their scavenging capacities in chemical combinatorial assays (expressed as IC50 values). We observed a 2-fold increase in the formation of ROS and LPX in the brain and liver after exposure to FeSO4, however when rats were pre-treated with AEPG (1 mg/kg for 21 days), these effects were significantly attenuated, obtaining similar values to the control group. The administration of AEPG increased, although not significantly, the cellular function values of brains that had been affected by the effect of FeSO4 from 52.84% to 75.53%, and with ONOO- from 51.25% to 79.20%. Punicalagin and ellagic acid induced a significant reduction of immobility at the lower doses used in this study (0.001 and 0.01 mg/kg). The capacity of scavenging compounds to eliminate radicals was as follows: for hydroxyl radical (•OH): AEPG > punicalagin > ellagic acid; for superoxide anion (O2•-): AEPG > punicalagin > ellagic acid; and for peroxynitrite (ONOO-): AEPG > punicalagin > ellagic acid. In conclusion, the AEPG promotes antidepressant-like actions that could be related to its antioxidant activity as it attenuated the oxidative damage and prevented cellular dysfunction in ovariectomized rat brains exposed to pro-oxidants ex-vivo. Some of these effects could be mediated by punicalagin and ellagic acid.